MARKETING POLITIK DPP PARTAI GERINDRA PADA PEMILU LEGISLATIF 2014 - Fahmi Nurdiansyah (Politika: Jurnal Ilmu Politik, 2018)
The purpose of this research is to know the implementation in the political marketing of Gerindra Party and some factors encouraging the party to gain a wide range of constituent voters in the legislative elections 2014. The aforementioned evidence reveals that Gerindra Party approached middle class down society and youth, on determining intended voters and this party also focusing on small society (farmer, fisherman, labour, teacher and small trader). In terms of positioning, Gerindra Party put themselves in outside of the government and acknowledge them as the party for small society. In Indonesian political constellation, it can be seen that political party has a high correlation with the power of public figure to increase popularity and electability. Gerindra Party is still introduced Prabowo Subianto as a public figure who can be used to gain a number of voters for the party.